Fractional Sobolev space with Riemann–Liouville fractional derivative and application to a fractional concave–convex problem - Ledesma C.E.T. (2021)
This work was partially supported by CONCYTEC PERU, 379-2019-FONDECYT “ASPECTOS CUALITATIVOS DE ECUACIONES NO-LOCALES Y APLICACIONES”